Rhinacanthin C Alleviates Amyloid-β Fibrils' Toxicity on Neurons and Attenuates Neuroinflammation Triggered by LPS, Amyloid-β, and Interferon-γ in Glial Cells. (18th October 2017) - Chuang, Kai-An; Li, Ming-Han; Lin, Ni-Hsuan; Chang, Chih-Hsuan; Lu, I-Huang; Pan, I-Hong; Takahashi, Tomoya; Perng, Ming-Der; Wen, Shu-Fang
Abstract : Neuroinflammation plays a central role in the pathophysiology of Alzheimer's disease (AD). Compounds that suppress neuroinflammation have been identified as potential therapeutic targets for AD. Rhinacanthin C (RC), a naphthoquinone ester found in Rhinacanthus nasutus Kurz (Acanthaceae), is currently proposed as an effective molecule against inflammation. However, the exact role of RC on neuroinflammation remains to be elucidated. In the present study, we investigated RC effect on modulating lipopolysaccharides (LPS), amyloid- β peptide (A β ), or interferon- γ - (IFN- γ -) evoked pathological events in neurons and glia. Our findings demonstrated that RC prevented A β -induced toxicity in rat hippocampal neurons and attenuated LPS-activated nitric oxide (NO) production, inducible nitric oxide synthase (iNOS) expression, and NF- κ B signaling in rat glia. Likewise, RC suppressed LPS-induced neuroinflammation by reducing NO production and iNOS, IL-1 β, CCL-2, and CCL-5 mRNA levels in rat microglia. Further studies using BV-2 microglia revealed that RC inhibited LPS-, A β -, and IFN- γ -stimulated IL-6 and TNF- α secretion. Of note, NF- κ B and ERK activation was abrogated by RC in BV-2 cell response to A β or IFN- γ . Moreover, RC protected neurons from A β -stimulated microglial conditioned media-dependent toxicity. Collectively, these data highlight the beneficial effects of RC on neuroprotection and support the therapeutic implications of RC to neuroinflammation-mediated conditions.